Licensure’s - Master’s – PhD system in the formation system in Nursing Professions and Health Techniques in the Kingdom of Morocco Between the challenges of the present and the stakes of the future - Louazi, Abdelouahid; El-battioui, Fadoua; Boukil, Noura; BEN ALLAL, Zohra (Journal of Economic, Administrative and Legal Sciences, 2025)
Objectives: This legal reading on the subject of Licensure’s - Master’s – PhD system in the formation system in nursing professions and health techniques  In the Kingdom of Moroccoaims to diagnose the current challenges and put forward the modern proposals in order to improve the quality of training in the higher institutes of nursing professions and health techniques and the legal systems associated with them.  Methods: This legal study adopted the critical analytical approach to evaluate the measures taken to download the requirements of the system of  Licensure’s - Master’s – PhD system in the formation system in the nursing professions and health techniques in Morocco, and the provisions of the set of legal texts on which this system is based and referred to in this study. Results: This brief study concluded to diagnose some of what can be considered current challenges to the process of reforming and adapting the formation system in the  nursing professions and health techniques In the Kingdom of Morocco with a Licensure’s - Master’s – PhD system mainly related to what is institutional, such as the slow work of the Foundation Council and its standing committees, and what is formative, such as the challenge of updating the content and methods of teaching and evaluation of training and the problem of field framing, as well as related to continuous training, scientific research and partnership, such as the lack of a clear strategic vision and action plans with feasible possibilities and horizon.  Conclusion: All these results lead to propose practical solutions to overcome the challenges facing the download of the new formation system such as reviewing the content of the training and its compatibility with scientific and pedagogical updates . Also these results will contribute to solve the problem of field framing, to accelerate the pace of the work of the Foundation Council and to expande the scope and the level of its consultation. Moreover, it will allow to prepare a work plan with a clear vision and better chances of implementing projects for the development of continuous training, scientific research and partnership.
Keywords: Challenges; Licensure’s - Master’s – PhD; Health Techniques; Nursing Professions; Stakes; Formation System; Morocco